Projeto e Validação de Sistema de Controle Embarcado para Análise de Desempenho de Algoritmos de Compensação Utilizados em Filtros Ativos de Potência - NICHOLAS DELBEN DE ANDRADE (2025)
This work compares the performance of the Instantaneous Power Theory and the Conservative Power Theory in generating compensation currents to correct Electrical Power Quality through Shunt Active Power Filters. Simulations are carried out in the Simulink environment, and also real-time simulation, taking advantage of the Hardware-in-the-Loop technique, through dSPACE and the DS1104 board. The power theories are embedded in the F28379D microcontroller to actuate in the real-time simulation and validate the embedded calculations. Furthermore, a cell phone app provided with Bluetooth communication and a local webserver with Wi-Fi communication were developed, with data communicated by an ESP32 microcontroller, respectively, in the MIT App Inventor and using the node-RED, for sending system data and the possibility of supervision. The correct generation of compensation currents in the main microcontroller was verified, in addition to the need for more robust real-time simulation hardware, enabling smaller simulation steps and better responses to rapid transients, especially in the scenario of loads with high harmonic distortion.